Data wrangling and analysis with Python - Jarmul, Katharine (Infinite Skills, 2016)
"Discover the data analysis capabilities of the Python Pandas software library in this introduction to data wrangling and data analytics. Designed for learners with some core knowledge of Python, you'll explore the basics of importing, exporting, parsing, cleaning, analyzing, and visualizing data. The course focuses on Pandas, where you'll learn to filter, group, match, and join data and then move on to advanced functions like analyzing trends and normalizing your data. There is also an introduction to some nifty skills like web scraping, working with API data, fuzzy matching, multiprocessing, and analyzing code performance."--Resource description page.